THE INFLUENCE OF WORK-LIFE BALANCE ON THE COMMITMENT AND MOTIVATION OF FEMALE EMPLOYEES IN THE HIGHER EDUCATION SECTOR IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
The core objective of this research paper is to delve into the impact of work-life balance on the commitment and motivation levels of female employees within the higher education sector in India. Women increasingly grapple with stress stemming from the dilemma of balancing home responsibilities and career advancement. This study primarily focuses on women employed in demanding roles, particularly in education. It seeks to uncover how work-life balance influences job satisfaction and commitment levels among these employees.Traditionally, women were confined to certain job roles like teaching, nursing, and secretarial positions. Recent studies indicate that utilizing resources like childcare centers and referral services can alleviate conflicts arising from work-life balance issues. The research employs empirical analysis to explore the challenges faced by women in achieving work-life balance, shedding light on issues such as cultural expectations, job performance, and peer dynamics.Moreover, the study delves into the influence of work-life balance factors on employee commitment within the education sector. Findings reveal that elements like the work environment, decision-making authority, personal role, support at work, and conflicts with colleagues significantly impact employee commitment in this sector.